Separation factors at sublimation refining of some lanthanides - Кravchenko, А.I. (Вопросы атомной науки и техники, 2020)
It is shown that the application of ideal separation factor in calculations of sublimation refining of Sm, Eu, Tm, and Yb has confined character: in considered base–impurity systems a difference between effective (β) and ideal (βi ) separation factors increases with deviation of βi from unity and can be very significant; the measurable difference (in limited of a one order) between β and ideal βi is observed at deviation of βi from unity not more than 2 orders. This does not contradict the conclusion on separation factors at distillation and sublimation of other substances. The discrepancies between the effective and ideal separation factors in evaporative refining processes (distillation and sublimation) are not associated with the chemical interaction of the components. Показано, що застосовність ідеального коефіцієнта розподілу в розрахунках сублімаційного рафінування Sm, Eu, Tm і Yb має обмежений характер: у розглянутих системах основа–домішка розбіжність ефективного (β) і ідеального (βi) коефіцієнтів розподілу зростає з відхиленням βi від одиниці і може бути вельми значним; помірна розбіжність β і βi (у межах одного порядку) спостерігається при відхиленні значень βi від одиниці не більше ніж на два порядки. Це не суперечить висновку про коефіцієнти розподілу при дистиляції і сублімації інших речовин. Розбіжності між ефективним і ідеальним коефіцієнтами розподілу у випарних процесах рафінування (дистиляція і сублімація) не пов'язані з хімічною взаємодією компонентів. Показано, что применимость идеального коэффициента разделения в расчетах высокотемпературного сублимационного рафинирования Sm, Eu, Tm и Yb имеет ограниченный характер: в рассмотренных системах основа–примесь расхождение эффективного (β) и идеального (βi) коэффициентов разделения растет с отклонением βi от единицы и может быть весьма значительным; умеренное расхождение β и βi (в пределах одного порядка) наблюдается при отклонении значений βi от единицы не более чем на два порядка. Это не противоречит заключению о коэффициентах разделения при дистилляции и сублимации других веществ. Расхождения между эффективным и идеальным коэффициентами разделения в испарительных процессах рафинирования (дистилляция и сублимация) при малом содержании примесей не связаны с химическим взаимодействием компонентов.